The Spatial Variation and Determinants of Age at First Marriage among Females in Riyadh City (Mutah Journal of Humanities and Social Sciences (MJHSS), 2026)
The study aimed to identify the pattern of age at first marriage in Riyadh City, and to analyze its spatial variation along with its demographic, social, and economic determinants. To achieve these objectives, a questionnaire was distributed to a sample of (496) married women. The data were analyzed using various statistical methods, including one-way ANOVA and T-tests. The study yielded several findings, most notably the high percentage of marriages occurring among females aged 18 to less than 25 years. The results further revealed that place of birth, family structure, education level, monthly income, and employment status had statistically significant effects on determining age at first marriage. Specifically, females from nuclear families and those with higher education tended to marry at later ages, whereas females with lower income levels were more likely to marry at younger ages. The results led to several recommendations, including conducting further research on changes in age at first marriage, particularly in light of the social and economic changes occurring in the Kingdom of Saudi Arabia, especially in Riyadh. Additionally, it recommends carrying out specialized surveys on the determinants of female age at first marriage in Saudi Arabia and examining their effects on social, economic, and health characteristics.
Keywords: Age; first marriage; females; spatial variation; nuclear families